Logic, language, information, and computation : 26th international workshop, WoLLIC 2019, Utrecht, The Netherlands, July 2-5, 2019, proceedings /: 26th international workshop, WoLLIC 2019, Utrecht, The Netherlands, July 2-5, 2019, proceedings. (2019) - Unknown
No abstract available